Construction of the myth of national hero: Eduardo Gomes and his performance in the tenentist Movement - Ferro, Flavia (Revista Crítica Histórica, 2018)
The article comprises the image construction of national hero Eduardo Gomes. The hypothesis is that the myth legitimized his Republic presidential candidacy by the União Democrática Nacional party in 1945 and 1950. The elaboration of the image was based on memories of his participation in the Levante do Forte de Copacabana and the Revolta tenentist de 1924, that is, in his determination as a revolutionary during the First Republic. However, it must be asked: who built the myth? What did the legend of a national hero do? How has society responded to the construction of the myth? This study, through the press and letters analysis, will answer these questions.